Ukrainian Journal of Food Science Vol. 1. Issue 1 - National University of Food Technologies (My University, 2013)
Ukrainian Journal of Food Science publishes original research articles, short communications, review papers, news and literature reviews dealing with all aspects of the food science, technology, engeneering, nutrition, food chemistry, economics and management. Ukrainian Journal of Food Science публікує оригінальні наукові статті, короткі повідомлення, оглядові статті, новини та огляди літератури з усіх аспектів харчової науки, техніки, інженерії, харчування, хімії, економіки та управління.
Keywords: харчові науки; техніка; хімія; економіка; управління; экономика; управление; пищевые науки; техника; химия; chemistry; management; food science; machinery; economy